2021
DOI: 10.2147/amep.s332797
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Oral Health Collaboration: A Survey of Knowledge and Practice Behaviors of Hospital-Based Primary Care Medical Providers in New York City

Abstract: Background:The siloed delivery of oral and medical health care in the United States has contributed to a lack of awareness of the consequences of poor oral health and has hampered effective interprofessional education and collaboration. The aim of this study was to assess the knowledge and practice behaviors of primary care medical providers in an urban safety-net hospital regarding collaboration with dentists and integration of oral health into overall health-care delivery. Methods: A 36-item survey was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…All pediatric medical residents, PNPs and FNPs who completed the year‐end online survey reported the program led to an increase in knowledge and skills to screen for ECC, provide anticipatory guidance to prevent dental caries and apply fluoride varnish to a child's teeth. These findings support previous research on the positive effects of programs on primary care providers’ oral health‐related knowledge, skills, and practice patterns 18,21,24–28 . There was a significant increase in mean scores from pre‐program to post‐program among pediatric medical residents, PNPs and FNPs who reported providing oral health anticipatory guidance during a patient visit.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…All pediatric medical residents, PNPs and FNPs who completed the year‐end online survey reported the program led to an increase in knowledge and skills to screen for ECC, provide anticipatory guidance to prevent dental caries and apply fluoride varnish to a child's teeth. These findings support previous research on the positive effects of programs on primary care providers’ oral health‐related knowledge, skills, and practice patterns 18,21,24–28 . There was a significant increase in mean scores from pre‐program to post‐program among pediatric medical residents, PNPs and FNPs who reported providing oral health anticipatory guidance during a patient visit.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies on oral health education programs for health care providers have indicated improvement in PNPs, general NPs, medical students, and internal medicine residents/physicians’ oral health‐related knowledge, attitudes, and skills. These studies have also shown that knowledge and skills learned in oral health education programs translated into changes in professional practice patterns regarding providing preventive oral health care services to their pediatric and adult patients and referring patients to dental providers when needed 16,20–28 . However, there continues to be little published research on oral health education in FNP programs 18,27 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Guidelines must be set to improve confidence in a provider's ability with regard to cases pertaining to both fields and have access to updated knowledge about the collaboration between medical and dental practice. 17,18 The existing body of medical and dental professionals play an important role since they have the ability to lay the guidelines. They can set guidelines for the indications, timing, protocols, and responsibilities of referral and consultation among physicians and dentists.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to knowledge-based questions, students were given seven questions, assessed via a Likert scale, regarding their familiarity with oral health topics, attitudes, and comfort regarding oral health care, providing oral health care education and guidance, and performing oral examinations on patients. These questions were adapted from validated questionnaires utilized by similar articles that assessed provider attitudes and comfort [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, currently oral health care and general health care in the United States (U.S.) are delivered in fragmented siloes. Care processes and workflows in the U.S. are compartmentalized between medicine and dentistry, which prohibits cooperation between practitioners and worsens healthcare outcomes for patients [ 6 , 7 ]. This fragmented United States healthcare delivery model is reflected in the oral health care education given to physicians.…”
Section: Introductionmentioning
confidence: 99%